FAIR TRADE DAN PERIKANAN TUNA DI INDONESIA (ANALISA PERAN YAYASAN MASYARAKAT DAN PERIKANAN INDONESIA) - Adi Putra Suwecawangsa; Putu Ratih Kumala Dewi (Universitas Pattimura, 2023)
Indonesia is one of the largest tuna producers in the world. In Indonesia tuna is produced by small-scale fishermen. This shows that small-scale tuna fisheries play an important role and as the mainstay of national food. However, the number of fish caught has not been followed by the welfare of small-scale fishermen. The exported tuna commodity also face difficulty in entering the market because it does not meet the requirements of the importing country, one of which is related to traceability. This is the concern of the Indonesian Fisheries and Community Foundation (MDPI). MDPI is a non-governmental organization that promotes fair trade-based fisheries in Indonesia. The evidence of fair trade fisheries implementation is through fair trade certification. The focus of this study is to analyze the role of the Indonesian Fisheries and Society (MDPI) in fair trade certification for tuna commodities in Indonesia. The research was conducted using descriptive qualitative research methods sourced from secondary data in the form of literature studies. In this study, the authors use the concept of the role of non-governmental organizations and fair trade. Researcher found that in fair trade certification for tuna commodities in Indonesia, the MDPI Foundation carries out three roles partner, implementer and catalyst. research is important to understand that non-governmental organizations play an important role in fair trade.